Properties and interfacial failure mode of surface modified polyimide fiber/epoxy composites - QIU Yang; LI Yafeng; TIAN Guofeng; ZHANG Mengying (Cailiao gongcheng)
To solove the problem of the low surface energy of polyimide（PI） fiber and poor interfacial performance between PI fiber and epoxy， atmospheric air plasma was selected to modify the surface of PI fiber. The influence of treatment duration on the surface structure of PI fiber and the interfacial properties of PI/epoxy composites was investigated. Effects of atmospheric air plasma on the surface micromorphology of PI fiber and failure plane of PI/EP composites were observed by the SEM. Dynamic contact angle and lateral tow tensile strength tests were chosen to characterize the infiltration effect and interfacial performance between PI fiber and epoxy after plasma treatment. The flexural strength and interlaminar shear strength tests were selected as inspection items for composites performance. The results implicate that atmospheric air plasma treatment can increase the infiltration and interfacial connection between PI fiber and epoxy， the lateral tow tensile strength of PI fiber modified by plasma treatment for 6 min is 16.05 MPa， with increment of nearly 21%. The increases in flexural strength and interlaminar shear strength of PI/EP composites are 36.41% and 38.85% respectively. Atmospheric air plasma modification can remake the surface morphology of PI fiber， and improve the joining effect of PI fiber and epoxy. Furthermore， the failure model of PI/EP composites is transformed from interfacial failure to fiber surface failure.